Forest-based livelihoods and downstream sedimentary organic carbon in the Tembawang Tampun Juah Customary Forest, West Kalimantan, Indonesia - ARIEF BUDI SETIAWAN; SYARIFUDDIN KADIR; MUHAMMAD NAPARIN; TRISNU SATRIADI; NUR YULIA SARI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Setiawan AB, Kadir S, Naparin M, Satriadi T, Sari NY. 2026. Forest-based livelihoods and downstream sedimentary organic carbon in the Tembawang Tampun Juah Customary Forest, West Kalimantan, Indonesia. Biodiversitas 27 (7): d270722. https://doi.org/10.13057/biodiv/d270722. Customary forests play important roles in sustaining local livelihoods while maintaining ecological functions, yet evidence integrating community-based livelihood information with downstream sediment characteristics remains limited. This study examined community-reported forest-based livelihoods and characterized sedimentary organic carbon at a selected downstream depositional site in the Tembawang Tampun Juah Customary Forest, West Kalimantan, Indonesia. Socioeconomic information was obtained through a single Focus Group Discussion (FGD) involving 20 purposively selected participants and analyzed using thematic interpretation, the People Value framework, and an indicative Net Present Value (NPV) approach. Hydrological measurements were conducted monthly from November 2024 to May 2025 at one downstream cross-section, whereas sediment samples were collected once from ten channel segments at three depths (5, 10, and 15 cm) and analyzed for organic carbon and selected physicochemical properties. The community-based economic assessment indicated a positive NPV of IDR 160,445,963 during 2015-2024, although exploratory Spearman analysis showed declining trends in annual profit and present value over time, suggesting reduced financial stability of forest-based livelihoods. Sedimentary organic carbon decreased slightly with depth, from 1.95±0.25% at 5 cm to 1.85±0.30% at 15 cm, while sediments remained consistently acidic and exhibited increasing silt and clay fractions with depth. Correlation analysis showed no significant association between mean stream discharge and sedimentary organic carbon or between cross-sectional area and sedimentary organic carbon. The observed sedimentary organic carbon pattern may therefore be associated with local sediment texture and depositional conditions rather than short-term hydrological variation alone. Because sediment observations were obtained from one downstream depositional site and socioeconomic information was derived from one consensus-based Focus Group Discussion, the findings should be interpreted as a preliminary site-specific socio-ecological assessment. These results provide an initial basis for integrating community livelihood information with downstream sediment assessment in customary forest management.